2022
DOI: 10.3390/app12189023
|View full text |Cite
|
Sign up to set email alerts
|

Whey Protein Isolate-Based Edible Coatings Incorporated with Jojoba Oil as a Novel Approach for Improving the Quality of Fresh-Cut Root Parsley during Refrigerated Storage

Abstract: In this paper, the effect of whey-protein-isolate-based edible coatings with the addition of jojoba oil at concentrations of 1 and 2% on the qualitative characteristics of fresh-cut root parsley was evaluated. Changes in hardness, color parameters, and the contents of polyphenols and flavonoids over 28 days of refrigerated storage, as well as changes in structure, were examined. It was observed that fresh-cut parsley, uncoated and coated with a protein solution, was characterized by a decrease in hardness, fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Glycerol is an example that can be used to improve the characteristics of an edible film with whey protein and is promising due to its ability to create a film with good mechanical and excellent oxygen barrier properties [173]. Other compounds are used for the same effect, such as jojoba oil, which was used in fresh-cut root parsley [174], Portuguese green tea extract for the preservation of Latin-style fresh cheese [162], ginger and rosemary essential oils to improve the quality of minced lamb meat [175], and others. Dianin et al [176] studied the creation of an edible coating with whey protein and the Lactobacillus casei probiotic for application in tomatoes and grapes and showed that this coating increases the shelf life of grapes but not of tomatoes, and the appearance of grapes was great for 14 days at 25 • C.…”
Section: Proteinsmentioning
confidence: 99%
“…Glycerol is an example that can be used to improve the characteristics of an edible film with whey protein and is promising due to its ability to create a film with good mechanical and excellent oxygen barrier properties [173]. Other compounds are used for the same effect, such as jojoba oil, which was used in fresh-cut root parsley [174], Portuguese green tea extract for the preservation of Latin-style fresh cheese [162], ginger and rosemary essential oils to improve the quality of minced lamb meat [175], and others. Dianin et al [176] studied the creation of an edible coating with whey protein and the Lactobacillus casei probiotic for application in tomatoes and grapes and showed that this coating increases the shelf life of grapes but not of tomatoes, and the appearance of grapes was great for 14 days at 25 • C.…”
Section: Proteinsmentioning
confidence: 99%
“…Hydrogel films based on milk proteins are characterized by good barrier properties to oxygen, flavors, and lipids as well as good mechanical properties [10,16]. However, due to the hydrophilic nature of whey proteins, coatings made from them exhibit a low barrier to water vapor [17]. Their composition also contributes to the enhancement of the nutritional properties of the coated food.…”
Section: Introductionmentioning
confidence: 99%